Following the Pathways of Greimas’ Mythology - Vaitkevičienė, Daiva (Tautosakos darbai, 2017)
Although several decades have passed since studies in mythology by Algirdas Julius Greimas Apie dievus ir žmones (‘Of Gods and Men’, 1979) and Tautos atminties beieškant (‘In Search of the National Memory’, 1990) saw publication, his pathway of mythological research has not been discussed in detail so far. The article contains chronological survey of Greimas’ works on mythology (including the ones published in French). The author highlights prerequisites and goals of Greimas’ studies on mythology and his attitude towards the situation of mythological research in Lithuania.Greimas’ earliest encounter with mythology and folklore is related with Lithuanian folklorist Jonas Balys. In the 1940s–1960s Greimas used to correspond with Balys, receiving folklore publications from him, and after having started publishing his works on Lithuanian mythology,engaging in discussions regarding his research methods. In 1949, Greimas published in theperiodical of Lithuanian diaspora Viltis his review of the research study and collection ofsources “Readings in Lithuanian Folklore” by Balys, and that was the first time he touchedupon issues of Lithuanian mythology.However, it was not friendship and discussions with Balys that channeled Greimas’ interest towards mythology. In the 1950s, his inspiration to study mythology stemmed from semiotic research: when developing his theory in semantics, Greimas used works on mythology, cultural anthropology, and folklore – among others, those by George Dumézil, Claude Lévi-Strauss, and Vladimir Propp. In 1963, 1965, and 1966 Greimas published theoretical articles on mythology. Lithuanian mythology attracted his attention in the late 1950s, when he wrote two works on semiotic theory based on the Lithuanian fairy tale belonging to the type AT 326 (“The Youth Who Wanted to Learn What Fear Is”). In 1972, his mythological study in Lithuanian appeared, focusing on analysis of kaukas and aitvaras (Greimas 1972). Afterwards, Greimas published all his research on mythology in Lithuanian. The sequence of rapidly appearing studies formed two books (Greimas 1979, 1990) that comprised all his most important contributions to mythology written in Lithuanian.Lithuanian mythology not only constituted an “experimental plot” for Greimas’ semiotic research, but also presented him with possibility of self-realization as a culture historian and researcher of religion. Besides, in his own words, he was thus paying his “debt to Lithuania”. On the other hand, he also attempted to open up the Lithuanian material to the research of the Indo-European culture. Greimas’ contribution to the studies of Lithuanian mythology and to the comparative research in mythology still awaits proper appreciation.
Keywords: -